2014
DOI: 10.1016/j.mcn.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

GluA2 mRNA distribution and regulation by miR-124 in hippocampal neurons

Abstract: AMPA-type glutamate receptors mediate fast, excitatory neurotransmission in the brain, and their concentrations at synapses are important determinants of synaptic strength. We investigated the post-transcriptional regulation of GluA2, the calcium-impermeable AMPA receptor subunit, by examining the subcellular distribution of its mRNA and evaluating its translational regulation by microRNA in cultured mouse hippocampal neurons. Using computational approaches, we identified a conserved microRNA-124 (miR-124) bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 65 publications
2
40
0
Order By: Relevance
“…Numerous studies on trans- channels, proteins with a role in actin dynamics, or scaffolding proteins. These mechanisms involve translation inhibition by microRNAs (Schratt et al, 2006;Ho et al, 2014), yet the mechanisms whereby specific factors disinhibit the microRNA remain unclear. Two studies have revealed interactions between mRNA binding proteins and microRNAs that regulate dendritic mRNA translation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on trans- channels, proteins with a role in actin dynamics, or scaffolding proteins. These mechanisms involve translation inhibition by microRNAs (Schratt et al, 2006;Ho et al, 2014), yet the mechanisms whereby specific factors disinhibit the microRNA remain unclear. Two studies have revealed interactions between mRNA binding proteins and microRNAs that regulate dendritic mRNA translation.…”
Section: Discussionmentioning
confidence: 99%
“…In neurons, mRNAs can be trafficked to distant sites in axons and dendrites for local translation and processing [52][53][54][55][56][57]. A range of neuronal transmembrane proteins, including AMPARs, NMDARs and GABA B Rs, can be translated using both somatic and dendritically localised ribosome patterned rough ER.…”
Section: Local Dendritic Translation and Secretory Pathway Traffickingmentioning
confidence: 99%
“…In live neurons, single molecule approaches have expanded our ability to explore the precise mechanism of RNA motility and localization [13,14]. Recent work highlighted here, utilizing single molecule fluorescence in situ hybridization (FISH) to endogenous mRNAs and live imaging of single mRNA in neurons has resulted in novel and at times even reformed insights into how mRNAs are localized in the brain [1517]. For the sake of simplicity, technologies which are capable of yielding single molecule resolution are discussed as single molecule imaging without focusing on whether this sensitivity was achieved in each study.…”
Section: Rna Localization In Neuronsmentioning
confidence: 99%
“…AMPA (α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) receptors, a type of glutamate receptor, may be composed of various combinations of subunits (GluA 1–4) and inclusion of the GluA2 subunit selectively diminishes the receptor’s permeability to extracellular calcium. Branched DNA labeling of endogenous mRNA showed that the GluA2 subunit mRNA of the AMPA receptor was not present in dendrites but instead was largely restricted to the soma [17]. In contrast, earlier studies reported dendritic localization of AMPA receptor subunit mRNAs (GluA1–4) and that subsequent synthesis of AMPA receptors could be modulated locally in an activity-dependent manner [7175].…”
Section: Seeing the Tree From The Forest – Changed Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation